Competition between Intra and Intermolecular Pnicogen Bonds: Complexes between Naphthalene Derivatives and Neutral or Anionic Bases. Issue 11 (26th April 2022) - Wysokiński, Rafał; Zierkiewicz, Wiktor; Michalczyk, Mariusz; Scheiner, Steve
Abstract: The PnF2 (Pn=P, As, Sb, Bi) on a naphthalene scaffold can engage in an internal pnicogen Pn⋅⋅⋅N bond (PnB) with an NH2 group placed close to it on the adjoining ring. An approaching neutral NH3 molecule can engage in a second PnB with the central Pn, which tends to weaken the intramolecular bond. The presence of the latter in turn weakens the intermolecular PnB with respect to that formed in its absence. Replacement of the external NH3 by a CN − anion causes a fundamental change in the bonding pattern, producing a fourth covalent bond with Pn, which rearranges into a trigonal bipyramidal motif. This addition disrupts the internal Pn⋅⋅⋅N pnicogen bond, recasting the PnF2 ⋅⋅⋅NH2 interaction into an NH⋅⋅⋅F H‐bond. Abstract : Pnicogen bonds : PnF2 (Pn=P, As, Sb, Bi) attached to a naphthalene scaffold is able to engage not only in an intramolecular pnicogen bond (PnB) with an NH2 group but in an intermolecular bond with a Lewis base as well.